2023
DOI: 10.3390/brainsci13030433
|View full text |Cite
|
Sign up to set email alerts
|

An EEG Study of the Influence of Target Appearing in the Upper and Lower Visual Fields on Brain Attention Resource Allocation

Abstract: Visuospatial selective attention can focus attention on a certain spatial area and rationally allocate attentional resources during visual target perception. Previous studies investigated the behavioral advantages of subjects when the target appeared in the upper and lower visual fields. However, the neurophysiological characteristics of the brain are not clear, and there is a lack of comprehensive analysis of the external behavior and the internal neurophysiological characteristics. We designed two task parad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…The P2 amplitude was more positive for the stress than the control group in both congruent and incongruent trials. The P2 component has been associated with the selective attention process triggered by the task-relevant stimulus, and the enhanced P2 indicated that more amount of attentional resources were allocated to the target stimuli ( Li et al, 2023 ; Luck & Hillyard, 1994 ; Zhou et al, 2019 ). The present results reflected that more amount of attentional resources might be allocated on processing of the visual stimuli under stress.…”
Section: Discussionmentioning
confidence: 99%
“…The P2 amplitude was more positive for the stress than the control group in both congruent and incongruent trials. The P2 component has been associated with the selective attention process triggered by the task-relevant stimulus, and the enhanced P2 indicated that more amount of attentional resources were allocated to the target stimuli ( Li et al, 2023 ; Luck & Hillyard, 1994 ; Zhou et al, 2019 ). The present results reflected that more amount of attentional resources might be allocated on processing of the visual stimuli under stress.…”
Section: Discussionmentioning
confidence: 99%
“…However, the neurophysiological characteristics of the brain are not clear. [29] Therefore, further research is required to address this issue. This study had several limitations.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of task performance and brain areas, previous studies investigated the behavioral benefits of participants regarding visuospatial selective attention. [ 29 ] Neurophysiological studies suggest a correlation between task performances and EEG signals. Parieto-occipital alpha (7–15 Hz; thought to modulate attentional focus) and frontal beta (13–30 Hz; associated with maintenance of the current sensorimotor state and predictive coding) oscillations covary with trial-wise percent-correct scores; importantly, alpha and beta power provide significant independent contributions to predicting single-trial behavioral outcomes.…”
Section: Discussionmentioning
confidence: 99%